SOIL FERTILITY AND QUALITY STATUS FOR BALANCED FERTILIZATION-BASED AGRICULTURAL LAND MANAGEMENT IN MENDOYO DISTRICT - Vandani, Yayan; Trigunasih, Ni Made; Sumarniasih, Made Sri (Jurnal Agrotek Tropika, 2025)
Soil fertility and quality have declined due to conventional farming practices that neglect fertilization. To restore soil fertility and quality, an evaluation is being conducted to determine balanced fertilization doses. This research aims to identify the soil fertility and quality status in the Mendoyo Subdistrict so as to provide recommendations for balanced fertilization in specific agricultural areas. The methods used were surveying and laboratory soil testing. The results demonstrated that the Mendoyo Subdistrict exhibited a combination of moderate and high soil fertility levels. The soils with moderate status were located in HLU (Homogeneous Land Units) I, II, V, VIII, IX, and X, while the those with high ones were located in HLU III, IV, VI, and VII. Moreover, the subdistrict exhibited varying levels of soil quality, ranging from poor to moderate, good, and very good. The poor-quality soil was located in HLU I, the good ones were located in HLU II, III, and IV, and the very good ones were located in HLU V, VI, VII, VIII, IX, X. The limiting factors in this research included texture, C-organic, nutrients (N, P, and K), and C-biomass. Meanwhile, the advanced regression and correlation tests indicated that C-organic was the most influential factor in determining soil fertility and quality, thus resulting in a recommended organic fertilizer dose of 2 t ha-1 for rice (Oryza sativa L), 15 kg plant-1 th-1 for cocoa (Theobroma cacao L) and robusta coffe (Caffea canephora), and 10 t ha-1 for coconut (Cocos nucifera) and banana (Musa paradisiaca L). Inorganic fertilizer doses vary depending on the soil's N, P, and K content.